Clinical profile, etiology and outcome of patients with pregnancy related acute kidney injury attending a tertiary care hospital in Goa, India - Mudasir Habib; Jai Prakash Tiwari; Hasil Mohammed Ali Edakkunnummel; Sumit Tyagi; Tejaswini Bhatlawande; Bipasa Kar (International Journal of Research in Medical Sciences, 2026)
Background: Pregnancy-related acute kidney injury (PRAKI) remains a significant contributor to maternal morbidity and mortality in developing countries, despite a global decline in incidence. Data from Indian tertiary care centers continue to demonstrate a predominance of preventable obstetric and infectious causes. Methods: This combined prospective and retrospective observational study included pregnant women aged 18-42 years diagnosed with PRAKI at Goa Medical College. Patients with pre- existing kidney disease were excluded. Demographic variables, obstetric profile, etiologies, severity of AKI (KDIGO criteria), need for renal replacement therapy, and renal outcomes were analyzed. Results: Seventy-two women were included, with a mean age of 30.6±5.5 years. Most patients presented in the third trimester (88.9%). Sepsis was the most common etiology (41.6%), followed by preeclampsia (22.2%) and postpartum hemorrhage (12.5%). Severe AKI predominated with 59.7% classified as KDIGO stage 3. Complete renal recovery occurred in 55.6% of patients, partial recovery in 26.4%, while 8.3% became dialysis-dependent. Overall mortality was 9.7%. Progression to chronic kidney disease (CKD) was observed in 35% of patients during follow-up. Conclusions: PRAKI continues to cause substantial renal morbidity and mortality. Sepsis and hypertensive disorders of pregnancy remain the leading etiologies. Early diagnosis, timely intervention, and long-term renal follow-up are crucial to improving outcomes.